Manganese impairs the QoxABCD terminal oxidase leading to respiration‐associated toxicity. Issue 3 (6th July 2021) - Sachla, Ankita J.; Luo, Yuanchan; Helmann, John D.
Abstract: Cell physiology relies on metalloenzymes and can be easily disrupted by imbalances in metal ion pools. Bacillus subtilis requires manganese for growth and has highly regulated mechanisms for import and efflux that help maintain homeostasis. Cells defective for manganese (Mn) efflux are highly sensitive to intoxication, but the processes impaired by Mn excess are often unknown. Here, we employed a forward genetics approach to identify pathways affected by manganese intoxication. Our results highlight a central role for the membrane‐localized electron transport chain in metal intoxication during aerobic growth. In the presence of elevated manganese, there is an increased generation of reactive radical species associated with dysfunction of the major terminal oxidase, the cytochrome aa3 heme‐copper menaquinol oxidase (QoxABCD). Intoxication is suppressed by diversion of menaquinol to alternative oxidases or by a mutation affecting heme A synthesis that is known to convert QoxABCD from an aa3 to a bo3 ‐type oxidase. Manganese sensitivity is also reduced by derepression of the MhqR regulon, which protects cells against reactive quinones. These results suggest that dysfunction of the cytochrome aa3 ‐type quinol oxidase contributes to metal‐induced intoxication. Abstract : Suppressor genetics was used to identify genes implicated in manganese intoxication in efflux‐defective Bacillus subtilis cells. Mn sensitivity is suppressed by loss of the major terminal oxidase (Qox complex), diversion of menaquinol to alternative oxidases, or derepression of the MhqR regulon, and is correlated with the level of DCF‐reactive radical species.